Dietary Nitrate Supplementation in Sport: Sources and Factors Influencing Ergogenic Effects - A Narrative Review - Kulak, Bartosz; Błaszczyk, Joanna; Brzeziński, Michał; Godyń-Müller, Kacper; Grześkowiak, Michał; Kasprzak, Mateusz; Majchrzak, Zuzanna; Pelant, Hanna; Klaudia, Pierzyńska; Zeigner, Martin (Journal of Education, Health and Sport, 2026)
Dietary nitrate supplementation has gained considerable attention as a potential ergogenic aid due to its ability to enhance nitric oxide bioavailability through the nitrate-nitrite-nitric oxide pathway. Increased nitric oxide availability may improve vascular function, mitochondrial efficiency, skeletal muscle contractility, and exercise economy, potentially enhancing exercise performance. This narrative review summarizes current evidence regarding the physiological mechanisms, dietary sources, supplementation protocols, and ergogenic effects of dietary nitrate supplementation in sport. Evidence indicates that nitrate supplementation may improve exercise economy, endurance capacity, and high-intensity exercise performance, particularly in recreationally active and moderately trained individuals. Emerging evidence also suggests potential benefits during resistance exercise and repeated sprint activities. However, the ergogenic response to nitrate supplementation appears to be highly variable and influenced by factors including training status, sex, habitual diet, oral microbiota composition, genetic polymorphisms, environmental conditions, and supplementation strategy. Current evidence further suggests that nitrate supplementation provides limited benefits in elite endurance athletes, women, and under hypoxic conditions. Acute ingestion of approximately 350-500 mg nitrate consumed 2-3 hours before exercise appears to represent the most effective supplementation strategy. Overall, dietary nitrate supplementation may provide ergogenic benefits under specific conditions; however, substantial inter-individual variability remains, and further research is required to develop personalized supplementation approaches.